2015
DOI: 10.1007/s10877-015-9805-5
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring sleep depth: analysis of bispectral index (BIS) based on polysomnographic recordings and sleep deprivation

Abstract: The assessment and management of sleep are increasingly recommended in the clinical practice. Polysomnography (PSG) is considered the gold standard test to monitor sleep objectively, but some practical and technical constraints exist due to environmental and patient considerations. Bispectral index (BIS) monitoring is commonly used in clinical practice for guiding anesthetic administration and provides an index based on relationships between EEG components. Due to similarities in EEG synchronization between an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 25 publications
(19 reference statements)
1
30
0
Order By: Relevance
“…Although PSG is the standard objective method for measuring sleep quality and quantity, its technical difficulty, high cost, and intolerability to patients make it impractical for its routine implementation in the ICU [11,12]. Although several studies have sought to report alternative methods of sleep monitoring, they have not yet been established [12][13][14][15]. The Richards-Campbell Sleep Questionnaire (RCSQ) is one of the simplest methods of subjective evaluation [3,12,16] and has been shown to correlate with PSG parameters [17].…”
Section: Introductionmentioning
confidence: 99%
“…Although PSG is the standard objective method for measuring sleep quality and quantity, its technical difficulty, high cost, and intolerability to patients make it impractical for its routine implementation in the ICU [11,12]. Although several studies have sought to report alternative methods of sleep monitoring, they have not yet been established [12][13][14][15]. The Richards-Campbell Sleep Questionnaire (RCSQ) is one of the simplest methods of subjective evaluation [3,12,16] and has been shown to correlate with PSG parameters [17].…”
Section: Introductionmentioning
confidence: 99%
“…[9] The bispectral index (BIS) can be used as a practical and simplified tool to evaluate natural sleep depth. However, BIS only can be used to identifying stage N3 with satisfactory sensitivity and specificity but is limited by its inability to distinguish REM sleep from wake.…”
Section: Introductionmentioning
confidence: 99%
“…PSG is the gold standard to sleep measurement (Gimenez et al, ), and the included study (Welcha et al, ) showed that family nurturing can increase frontal brain activity during sleep, which can help to understand the mechanism of the intervention more clearly. However, few studies used this objective sleep measurement in this review.…”
Section: Discussionmentioning
confidence: 99%